Otoscopic and Radiographic Examination of Dogs Suffering From External Ear Affections - Gaur, Megha; Jain, Reshma; Shukla, Brahm Prakash; Shrivastava, Nidhi; Parihar, Atul singh; Kaushik, Vishal (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Otoscopic and radiographic examinations are effective tools to diagnose the ear affections like otitis externa, chronic hypertropic otitis externa, neoplasia, pathological changes of ear canal and other conditions. Hence, present study was planned to record the clinical cases of dogs suffering from external ear affections with survey otoscopic and radiographic examination. The otoscopic examination of 84 dogs revealed presence of different types of texture and discharge in the ear canal. Different changes on the inner wall of external ear canal evident on otoscopic examination were erythema, ulceration, hyperplasia of inner wall, hyperplasia of ceruminous glands, presence of excessive hair and polyp. Survey radiography revealed stenosis, calcification of ear canal, bilateral involvement of ear and increased opacity of the tympanic bulla. Otoscopy and radiography are practical and accessible tools for detecting changes in the ear canal and other related structures.